The Effect of Profitability Ratio on Stock Price - Fitri Dwi Jayanti (Universitas Ngudi Waluyo, 2021)
The purpose of this study was to examine and analyze the effect of profitability ratios consisting of Net Profit Margin (NPM), Return on Assets (ROA), Earning Per Share (EPS) on stock prices in the Food and Beverage Sub-sector Manufacturing companies listed in Indonesia Stock Exchange (IDX) in 2017-2019. The sample in this study were 45 companies that were taken using the purposive sampling method. One of the factors that can increase the value of a company's shares in the capital market is good financial performance. This is because good financial performance can give investors confidence to invest their shares in the company.